Single visits to active wolf dens do not impact wolf pup recruitment or pack size ... - Gable, Thomas D; Johnson-Bice, Sean M; Homkes, Austin T; Bump, Joseph K (Data Repository for the University of Minnesota (DRUM), 2024)
Dataset for Gable et al. where the authors used a quasi-experimental approach (reference vs. treatment) to determine whether visiting wolf dens and marking wolf (Canis lupus) pups affects important wolf population metrics. Specifically, Gable et al. examined whether pup recruitment and pack size differed between packs where they visited dens and handled pups (‘disturbed packs’ = treatment group) and those where they did not visit dens (‘undisturbed packs’ = reference group). During 2019-2023, they studied 43 wolf packs and litters, 19 of which were disturbed packs and 24 of which were undisturbed. They found no difference in recruitment or pack size between disturbed and undisturbed wolf packs. However, they did observe substantial annual variation in recruitment and pack size, which indicated that other ecological factors (e.g., prey abundance) were likely responsible for annual changes in recruitment and pack size. Their findings are consistent with several other studies, and together this research ... : We have uploaded a README file. ...